PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Bengkalis) - Claura, Anggie Veronisa; Taufik, Taufeni; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of the application of performance-based budgeting affect the performance accountability of government institutions Bengkalis district uses four variables, namely, the competence of the government apparatus (X1), organizational commitment (X2), leadership style (X3), and reward and punishment (X4). The population in this study is 31 working units Bengkalis. Samples taken amounted to 93 respondents. The type of data used are primary data with data collection method using a questionnaire. Data analysis method used in this study is multiple regression and regression moderate with SPSS version 17.Results of this study indicate that the government because tcount <t¬tabel 0.387 <1.997 with significant values of 0.05, Organizational Commitment significant effect on performance accountability of government agencies because thitung> t¬tabel2,538> 1.997 with 0:05 significant value, leadership style have a significant effect to the accountability of agency performance because tcount <t¬tabel1,997 with significant values of 0.05 and the reward and punishment have a significant effect on performance accountability institutions because thitung <t¬tabel4,465 <1.997 with significant value of 0.05. With a total number of 0,646 R2square value of 64.6% which means that the independent variable in this study could affect the dependent variable, while the remaining 35.4% is explained by other variables not included in this study such as the improvement of the administration system, the quality of human resources, obedience on the laws, organizational culture, the application of financial accountability, performance contracts, performance measurement, internal and external control.Keywords: Budgeting, Apparatur, Accountability and Government.